Keeping secrets: how children in foster care manage stigma. (March 2019) - Dansey, Diane; Shbero, Danielle; John, Mary
This article follows on from 'How children in foster care engage with loyalty conflict: presenting a model of processes informing loyalty' (Dansey, John and Shbero, 2018 ), published in the previous edition of this journal. This model highlighted the themes of stigma and secrecy for children in care, which it was felt warranted further consideration in their own right. The current article shares further quotations from the children in relation to these themes, which add to the evidence of what children are saying in relation to stigma and bullying. Most importantly, it presents this topic in a manner that stimulates thought around the implications of what children are saying for their broader mental health and resilience and what might therefore be most supportive.  Children in foster care are subject to stigma in relation to being in care and not living with their birth parents. The impact of this is important to explore, especially for those who already experience higher levels of disadvantage than other children. Themes of stigma and secrecy emerged from a recent grounded theory study that was conducted with 15 children and young people in foster care (Dansey, John and Shbero, 2018 ). These quotations highlighted how stigma was being internalised by children, how they had experienced, or believed that their care status would lead to, bullying and how some of them described keeping their foster care status a secret as a result. This article seeks to share the voices of these children, look at the existing literature in this area and consider the possible impact that stigma and secrecy may have on them. Implications for practice are discussed and the need for more targeted research is highlighted.